Tension Estimation Method for Cable With Damper Using Natural Frequencies With Uncertain Modal Order - Furukawa, Aiko; Suzuki, Syuya; Kobayashi, Ryosuke (Frontiers in Built Environment, 2022)
In the maintenance of cable structures, such as cable-stayed bridges, it is necessary to estimate the tension acting on the cables. In current Japanese practice, the cable tension is estimated from the cable’s natural frequency using vibration-based methods. However, in recent years, dampers have been installed onto the cables to suppress aerodynamic vibrations. Because the damper changes the cable’s natural frequencies, the methods used for cables without dampers are not appropriate for cables with dampers. With this background, the authors previously proposed a method (Method 0F) for estimating the tension of a cable with a damper from the natural frequencies and their modal order. Method 0F partially ignores the imaginary part of the complex natural frequencies to simplify the problem. This paper proposes a new method (Method 1F) that does not ignore the imaginary part of a complex natural frequency. Method 1F still needs both the natural frequencies and their modal order to be input. If the modal order is not correctly specified, the accuracy deteriorates. Therefore, a new method (Method 2F) that only requires the natural frequencies is also proposed. The validity of the proposed methods was confirmed by numerical simulations and experiments. The numerical and experimental verifications confirmed that the new methods were superior compared with previous methods, and that method 2F has the highest effectiveness.